Routing in IPv6 over Low-Power Wireless Personal Area Networks (6LoWPAN): A Survey - Vinay Kumar; Sudarshan Tiwari (Journal of Computer Networks and Communications)
6LoWPANs (IPv6-based Low-Power Personal Area Networks) are formulated by devices that are compatible with the IEEE 802.15.4 standard. To moderate the effects of network mobility, the Internet Protocol (IP) does not calculate routes; it is left to a routing protocol, which maintains routing tables in the routers. 6LowPAN uses an adaptation layer between the network (IPv6) and data link layer (IEEE802.15.4 MAC) to fragment and reassemble IPv6 packets. The routing in 6LoWPAN is primarily divided on the basis of routing decision taken on adaptation or network layer. The objective of this paper is to present a state-of-the-art survey of existing routing protocols: LOAD, M-LOAD, DYMO-Low, Hi-Low, Extended Hi-Low, and S-AODV. These routing protocols have compared on the basis of different metric like energy consumption, memory uses, mobility, scalability, routing delay, an RERR message, a Hello message, and local repair. We have also presented the taxonomy of routing requirement; parameter for evaluating routing algorithm, and it was found that the routing protocol has its own advantages depending upon the application where it is used.